CURRENT ISSUES OF DEVELOPING INCLUSIVE EDUCATION IN EDUCATION POLICY - Tilakova M. A. (Journals Park Publishing, 2024)
The article focuses on the pedagogical and psychological aspects of education for children with disabilities through inclusive education, provides information on the tasks carried out to the aamla on accelerating intellectual development, training of competitive personnel, effective organization of scientific and innovative activities, and the focus on educational processes and inclusive education today.
Keywords: The study of Inclusive Education is one of the New, most pressing problems in pedagogical science, the effective use of masterpieces of National Education, the upbringing of healthy and disadvantaged children as manic perfection, an individual attitude – the way to influence the student.